Juridical Review of Regional Head Election Campaigns in Universities - Belladina Putri Aryani Kusnandar; Hananto Widodo; Widodo Partono (Indonesian Journal of Administrative Law and Local Government, 2024)
The prohibition in the Regional Head Election campaign has actually been regulated in Article 69 letter i of Law Number 1 of 2015 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents, and Mayors into Law. In line with the time, there was an application for judicial review of the article a quo in which the Plaintiffs argued that they suffered constitutional losses. The constitutional judge granted the Petitioners' petition in its entirety through the Constitutional Court Decision Number 69/PUU-XXII/2024. The purpose of this study is to analyze and describe the racio dacidendi of the constitutional judge who granted the Petitioners' petition in its entirety along with the legal consequences of the Regional Head Election campaign in higher education. The type of research used in this research is normative juridical research with a research approach, namely a statute approach, case approach, and conceptual approach. The legal materials used are primary, secondary, and tertiary legal materials. The results of this study show that constitutional judges use historical (original) interpretation. However, the existence of the decision a quo actually creates a norm conflict with Article 8 paragraph (1) of Law Number 12 of 2012 concerning Higher Education. In addition, there are also violations of the principles stipulated in Article 3 of Law No. 12 of 2012, namely the principle of benefit, the principle of virtue, and the principle of responsibility. There are suggestions from researchers as a form of recommendation, namely the Constitutional Court needs to encourage the House of Representatives as the legislator to immediately revise the Regional Head Election Law to ensure legal certainty and also emphasize the importance of protecting the academic community from the potential influence of practical politics in the university environment and the House of Representatives needs to immediately revise the Pilkada Law to be in line with the Constitutional Court Decision No. 69/PUU-XXII/2024. Keywords: Campaign, Regional Head Elections, Constitutional Court Decision, Higher Education, Academic Community.